Self Regulated Learning dan Locus Of Control Siswa Ditinjau dari Jenis Kelamin danLatar Belakang Budaya - Sari, Ayu Permata; Nirwana, Herman; Ahmad, Riska (Universitas Negeri Padang, 2015)
One of the BK's teacher roles at school is optimize the learning result of student. Self regulated learning (SRL) and locus of control (LOC) are the factors that greatly influencethe learning result of student. This research is based on inconsistency research innovating about SRL and LOC ofmen and women from all kind of the cultures in Indonesia. The goals of this research are:Â (1) to describe SRL and LOC (2) to examine the differences of SRL and LOC of the studentsÂ based on sex and cultural background.This research is quantitative descriptive and comparative. The populations are student at SMAN 1 Batusangkarand at SMAN 1 Balige(2015-2016). The sample were taken by using random sampling technique, the total of the sample is 350 students. Data were analyzed by percentage and MANOVAtechnique.The result of this research show that (1) SRL are quite good and LOC is belong to internalization (2) there is no significant difference of students who have Minangkabau and Batak, there are significant difference on SRL of male and female students in Minangkabau, and LOC there is not difference, there are significant differences in SRL of male and female students in Batak, and LOC is no difference, there are no significant differences on men and women in Minangkabau and Batak. The implications of the results of this research can be used as input to create a program of guidance and counseling services, especially in the development of learning.